2022
DOI: 10.1039/d2ce00094f
|View full text |Cite
|
Sign up to set email alerts
|

Structural systematics in isomorphous binary co-crystal solvates comprising 2,2′-dithiodibenzoic acid, 4-halobenzoic acid and dimethylformamide (1 : 1 : 1), for halide = chloride, bromide and iodide

Abstract: The 1:1:1 binary co-crystal solvates formulated as 2,2'-dithiodibenzoic acid (DTBA), 4-halobenzoic acid (4-XBA) and dimethylformamide (DMF) for X = Cl (1), Br (2) and I (3) are isomorphous and the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The most successful strategies to date employed inclusion compounds, , or cocrystallization using series of coformers equivalent with respect to the geometry of the molecule and potential for intermolecular assembly. Because of the success of some of these approaches, it has also been suggested that isomorphism is generally more likely in multicomponent crystals. …”
Section: Introductionmentioning
confidence: 99%
“…The most successful strategies to date employed inclusion compounds, , or cocrystallization using series of coformers equivalent with respect to the geometry of the molecule and potential for intermolecular assembly. Because of the success of some of these approaches, it has also been suggested that isomorphism is generally more likely in multicomponent crystals. …”
Section: Introductionmentioning
confidence: 99%
“…31,32 Prominent among these are S-benzyl esters 33 as are pyrrolidine dithiocarbamates. [34][35][36] As an extension of work exploring the potential biological activity of metal dithiocarbamates, including pyrrolidine derivatives, [37][38][39] and systematic studies of molecules that differ only in the nature of a small substituent, [40][41][42][43] a series of five S-benzyl esters of pyrrolidine dithiocarbamate were investigated which differ in the nature of the substituent in the 4-position of the terminal phenyl group. Of particular interest was to ascertain how systematically changing the halogen atom influences the molecular packing.…”
Section: Introductionmentioning
confidence: 99%